BIOTEKNOLOGI SEBAGAI PENUNJANG PERTANIAN BERKELANJUTAN - Susilowati, Retno (Jurnal Bestari, 2001)
There is no nation can maintain the economical growth process without solving food endurance problem exceedingly. The economy of rice is significantly proponent of the economic growth in Indonesia. Therefore, the continuous agriculture system utilizes the modern farming equipments, the qualified seed, and the conservational practices of water and soil. Its emphasis on the plant rotation, the soil process becomes better, the food plants diversification, and the naturally pest control.